2009
DOI: 10.1111/j.1365-2036.2009.03968.x
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model of colonic concentrations of delayed‐release 5‐aminosalicylic acid (Asacol)

Abstract: SUMMARYBackround 5-ASA in a pH sensitive tablet (Asacol) is administered as three doses ⁄ day to treat ulcerative colitis. Once daily dosing may improve patient adherence. Simulation of colonic levels of 5-ASA can be used to compare dosing regimens. AimTo create a dynamic model of colonic concentrations of delayed-release 5-aminosalicylic acid (Asacol). MethodsUsing published data, we created a computer model with STELLA software to simulate amounts of colonic 5-ASA in the total colon, right, transverse, desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Thorpe et al [60], using a dynamic model of colonic concentrations that mimics published transit time data, reported that the distribution of 5-ASA within the colon was shown to change in response to a change in motility patterns with reduced motility resulting in higher concentrations of 5-ASA [60] which is also consistent with data from our model. This work considered a simple immediate release formulation as a first step in the development of the model.…”
Section: Strengths and Limitations Of The Modelsupporting
confidence: 88%
“…Thorpe et al [60], using a dynamic model of colonic concentrations that mimics published transit time data, reported that the distribution of 5-ASA within the colon was shown to change in response to a change in motility patterns with reduced motility resulting in higher concentrations of 5-ASA [60] which is also consistent with data from our model. This work considered a simple immediate release formulation as a first step in the development of the model.…”
Section: Strengths and Limitations Of The Modelsupporting
confidence: 88%
“…The effectiveness of the drug is related to its mucosal concentration, 10 the type of release formulation (e.g. pH‐dependent) and the individual intraluminal pH as well as motility 11 . On a molecular level, 5‐ASA inhibits cyclooxygenase‐2 (COX‐2)/prostaglandin E2 synthesis, 12,13 decreases transcriptional activity of NF‐κB by modulating RelA/p65 phosphorylation 14 and interferes with Wnt pathway through protein phosphatase 2A (PP2A) 15 …”
Section: Introductionmentioning
confidence: 99%
“…pH-dependent) and the individual intraluminal pH as well as motility. 11 On a molecular level, 5-ASA inhibits cyclooxygenase-2 (COX-2) ⁄ prostaglandin E2 synthesis, 12,13 decreases transcriptional activity of NF-jB by modulating RelA ⁄ p65 phosphorylation 14 and interferes with Wnt pathway through protein phosphatase 2A (PP2A). 15 Although clinical evidence for chemopreventive effects of 5-ASA in patients with IBD suggests specific anti-inflammatory or oxygen scavenging properties, this drug seems to possess multiple modes of action which, despite numerous experimental studies, remain partially unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the use of STELLA modeling in the medical literature include benefit estimates of treatment options in pediatric patients with Crohn's disease [30] , and utility of information technology for prevention of adverse drug events [31] . Our group has previously applied STELLA modeling to predict colonic levels of topically active gastrointestinal drugs that are unmeasurable using conventional techniques [32] . We chose this method in the current study because objective values for several parameters built into the model were either not available in the medical literature, or needed to be estimated from findings in other patient groups, (such as MSM).…”
Section: Discussionmentioning
confidence: 99%